How can Japan help create a sustainable hydrogen society in Asia? - Nandakumar Janardhanan; Mustafa Moinuddin; Eric Zusman; Hajime Takizawa; Kentaro Tamura (Asian Development Bank Institute (ADBI), 2023)
Japan has adopted several policies that signal its intent to rely on hydrogen to achieve net-zero climate goals. However, many of those same policies are unclear about its support for a transition to green hydrogen. Relying on gray and blue hydrogen without a transition to green hydrogen will harm the climate. It will also result in several other lost international cooperation and local socioeconomic benefits. This paper argues that greater clarity about the transition to green hydrogen will help strengthen the alignment with Japan's international climate strategy and local revitalization policies. It then proposes a set of recommendations that can clarify its support for transitioning to green hydrogen in national policies as well as international climate and local revitalization strategies.
Keywords: Q42; Q48; Q49; 330; hydrogen; co-innovation; net zero; green hydrogen; Japan; Asia